Phytase Production by Lactobacillus plantarum A1-E in Submerged and Solid-State Fermentation - Ade Erma Suryani; Lusty Istiqomah; Ayu Septi Anggraeni; Anjar Windarsih Windarsih (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Enzyme activity is influenced by several important factors, including the amount and type of substrate, solvent type, pH, temperature, presence of inhibitory and activating ions, and concentration of enzymes. Therefore, this research aimed to evaluate phytase production from Lactobacillus plantarum A1-E using submerged (SmF) and solid-state fermentation (SSF). Phytase production was determined using SmF with fructose and sucrose as the primary carbon sources at concentrations of 4.5%, 6%, and 7.5%. Additionally, SSF was conducted using three distinct substrates, including soybean Meal, rice Bran, and pollard. The results indicated that the highest phytase activity was achieved through SSF when rice bran was used as a substrate (88.48 U/mL or 4.65 U/mg). The use of 4.5% sucrose as a carbon source in the SmF technique showed the highest specific phytase activity (4.38 U/mg) compared to other carbon sources at various concentrations. The addition of metal ions showed that Fe 2+ , Mn 2+ , and Co 2+ at concentrations of 1-5 mM, Mg 2+ and Zn 2+ at concentrations of 3-5 mM, and Ca 2+ at a concentration of 3 mM acted as activators that increased phytase activity compared to control. Meanwhile, Mg 2+ and Zn 2+ at concentrations 1-2 mM were inhibitors.